Helicobacter Pylori Seropositivity and Acute Myocardial Infarction - Abdul-Gafour, Wathiq K.; Baqir, Haitham I; Al-Raubyee, Riyadh S (AL-Kindy College Medical Journal, 2011)
Background: Acute myocardial infarction(AMI) is one of the most common diagnosesin hospitalized patients. The stimulus thatinitiates the acute inflammatory process in AMIhas not been identified. Conventional riskfactors account only for approximately half ofthe patients with clinically apparentatherosclerosis which can leads to AMI.Recently a potential link between infectiousagents and atherosclerosis has been suggested Objective: To find a possible associationbetween Helicobacter pylori (H. Pylori)infection and AMI. Method: We studied the prevalence of antiH. pylori antibodies in 94 patients who wereadmitted with the diagnosis of AMI and asimilar number of healthy individuals who wereage and sex matched. This was done usingELISA technique. Results: Overall prevalence of anti-H. pyroliantibodies in patients with AMI was 82.9%whereas the prevalence in the control groupwas 78.7% . This difference yielded an odd ratioof 1.317. Chi square test shows that thisdifference was insignificant statistically (p-value0.458) Conclusion: We feel that our results do notsupport the hypothesis which stated that chronicinfection with H. pylori is a major risk factor forAMI.